Ad-Hoc Business Intelligence for Agile Decision-Making: A Case Study Using Adventure Works 2022 - Maulidati, Zuli; Pangestu, Satrio Bagas; Aini, Salma Nur (INTEGER: Journal of Information Technology, 2025)
Agile decision-making in today's business is highly crucial for an organisation to stay competitive. Business intelligence has overcome the situation to provide solutions in any crucial condition. Unlike the static dashboard, the ad hoc dashboard is considered to be a viable solution in tailoring business to make a data-driven decision with a high flexibility. This study aims to examine and implement ad-hoc dashboards using the Adventure Works 2022 dataset. The result of the study shows that both dashboards implement interactive filtering, drill-down capabilities, and real-time visualization to enhance data-driven decision-making agility. The design of dashboard A provides a structured, multi-dimensional view suitable for in-depth analysis; meanwhile, dashboard B prioritises simplicity and accessibility, presenting key insights intuitively for quick decision-making. Furthermore, the study highlights the result that the biggest challenges of building a dashboard are information overload and usability. It is important to note that the implementation of ad-hoc BI should balance between analytical capabilities and user-friendliness to ensure that dashboards provide meaningful insights and are easy to use by end users. Keywords: Ad-hoc BI, Agile Decision Making, BI Dashboard